Occurrences of macrobenthic organisms collected from van Veen grab and box corer samples taken in the waters off western Spitsbergen between 1991 and 2007 - Maria Wlodarska-Kowalczuk; Jennifer Dannheim; Dieter Piepenburg (PANGAEA, 2024)
This dataset is a component of the PAN-Arctic data collection of benthic BIOtas (PANABIO). It contains a total of 1,332 presence records of 265 macrobenthic taxa (species to genus level) identified in 24 van Veen grab and two box corer samples taken at 26 stations located off western Spitsbergen at water depths of 50–525 m during six cruises between 1991 and 2007. The dataset is also available in a PostgreSQL-based data warehouse that can be accessed and queried through an open-access frontend web service at https://critterbase.awi.de/panabio.
In: Piepenburg, Dieter; Brey, Thomas; Teschke, Katharina; Dannheim, Jennifer; Kloss, Paul; Hansen, Miriam Lea Sarah; Kraan, Casper (2023): PANABIO: A point-referenced pan-Arctic data collection of benthic biotas [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.963640